The Legal Issues of Linking Job Grade to Job Title and Ways to Address Them in Iraqi law - Ismael, Anas (Journal of Legal Sciences, 2025)
This research examines the legal problems resulting from the mandatory link between job grade and job title in the Iraqi employment system. The research is divided into two main sections. The first section focuses on diagnosing the problem, starting with defining the promotion and advancement systems, and analyzing the problematic nature of the mandatory link between them. It then discusses the negative effects of this linkage, which may include hindering the career path of outstanding employees whose jobs do not include high-level titles, weakening competency standards for promotion, imbalances in the distribution of tasks and responsibilities, and bureaucratic appointments and vacancies. The second section presents ways to address this problem. In its first section, it presents proposed legislative solutions, such as separating the financial promotion path from the title promotion path in the law, and establishing flexible promotion systems that depend on performance and efficiency standards instead of being exclusively linked to the title. The second section concludes with a discussion of the proposed executive mechanisms for implementing these solutions, which include mechanisms for evaluation and periodic review to ensure the success of the process of separating the two systems and achieving justice and efficiency in human resources management in the public service. The ultimate goal of the research is to advocate for reforming the career system by separating the financial promotion path from the job title to motivate competencies and achieve job fairness.